Peran FDI Tiongkok dalam Mendorong Pertumbuhan Ekonomi Indonesia di Era Ketidakpastian Global - Nindya Eka Sobita; Muhammad Mufti Hudani; Vitriyani Tri Purwaningsih; I Wayan Suparta; M Iqbal Harori (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
Abstract. This study aims to analyze the short-term impact of Chinese Foreign Direct Investment (FDI), government expenditure, and Gross Domestic Product (GDP) based on expenditure on Indonesia's economic growth amid global uncertainty during the 2010–2024 period. A quantitative approach was employed using time series regression with the Ordinary Least Squares (OLS) method. Prior to model estimation, data were tested for stationarity using the Augmented Dickey-Fuller (ADF) test. The results show that simultaneously, the three independent variables significantly influence economic growth. Partially, Chinese FDI has a positive and marginally significant effect, government expenditure shows a significant negative impact, while household consumption-based GDP exerts a strong and statistically significant positive influence on Indonesia's economic growth. These findings highlight the critical role of domestic consumption and effective government spending in promoting growth, as well as the need to enhance the quality of foreign investment. Keywords: Chinese FDI, economic growth, government expenditure, consumption.